Assessment of polyclonal derivatives for morphological traits and hybridity analysis using SSR markers in cocoa (Theobroma cacao L.) - Jegadeeswari, V; Padmadevi , K; Vijayalatha, K.R; Suresh, J (Plant Science Today, 2025)
Cocoa (Theobroma cacao L.) is increasingly cultivated as an intercrop in South India, necessitating the development of high-yielding, region-specific varieties. As a self-incompatible crop, establishing polyclonal orchards with cross-compatible varieties and producing full-sib hybrids through controlled pollination is vital for genetic improvement. Evaluation of half-sib and full-sib progenies was undertaken in polyclonal cocoa gardens situated at Coconut Research Station, Aliyar Nagar and Horticulture Research Station, Thadiyankudisai, under the auspices of Tamil Nadu Agricultural University. Pods developed from the natural cross and cross-made using caging techniques were evaluated, and seeds were sown to assess the performance of the hybrids. The findings illustrated the highest germination percentage in the half-sib cross CCRP 5 × X (89.66 %), followed by CCRP 4 × X (85.57 %). The highest value for plant morphological characters like plant height (2.11 m), stem girth (15.7 cm) and jorquette height (1.58 m) was recorded in CCRP 5 × X. Among the full-sib progenies, the highest germination percentage (86.1) was recorded by FS 17 (CCRP 3 × CCRP 5), followed by FS 18 (CCRP 5 × CCRP 3) (81.8). The hybridity of the seedlings was tested using SSR markers, which confirmed that out of 26 full-sib crosses, 16 exhibited a heterozygous nature. These findings demonstrate the potential of selected progenies to serve as valuable genetic resources for breeding programs aimed at enhancing cocoa productivity and sustainability in South India.